Predicting Logarithm of Real Numbers to any Real Number Base - Asfaque, Mohammad; Kafle, Jeevan (Mathematics Education Forum Chitwan, 2021)
This paper aims to propose an algorithm that can predict the values of logarithmic function for any domain and for any bases with minimum possible error using basic mathematical operations. It talks about a univariate quadratic function that overlaps with the graph of the common logarithmic function to some extent, and using this resemblance to fullest advantage. It proposes a formula and certain algorithms based on the same formula.